A study on the determinants of Malaysian banks’ profitability / Sharifah Mastura Syed Mohsin - Syed Mohsin, Sharifah Mastura (2015)
The aim of this study is to determine the pattern of bank characteristic (internal) and macroeconomic (external) determinants on the profitability of Malaysian banks. Internal determinants include bank size, capital adequacy ratio, liquidity, asset quality, and expenses management; while the external determinants comprise of gross domestic product (GDP), inflation, money supply, and competition. Secondary data was collected mostly from Bank Negara Malaysia (BNM) Catalogue which consists of both conventional and Islamic banks together in a single data set from year 2007 to 2013. The financial ratios technique was applied to calculate on these variables and Ordinary Least Square (OLS) method was used to run the regression model. The estimation result shows that liquidity is the only variable that is significant but negatively influences the banks’ profitability. For future studies, it is recommended that more sample size and determinant factors can be included in determining the factor on bank profitability.